2016
DOI: 10.1037/com0000039
|View full text |Cite
|
Sign up to set email alerts
|

Explorative innovators and flexible use of social information in common ravens (Corvus corax) and carrion crows (Corvus corone).

Abstract: Innovation and social information use are influenced by individual characteristics, and are important for the creation and transmission of novel behavioral patterns. Here, we investigated which individual factors predict innovation rates and social transmission of information in a comparative study with identically reared common ravens (Corvus corax) and carrion crows (Corvus corone corone; Corvus corone cornix). In the innovation experiment (1), we presented the birds with a novel problem-solving task while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Two of seven jays (one male, one female) chose the same coloured cup (white) as the demonstrator (i.e., copied the demonstrator), while the other five jays (three females, two males) chose the non-demonstrated cup colour (black; Table 3). In comparison, Miller, Schwab & Bugnyar (in press) found that eight of eight crows (five females, three males) and eight of eight ravens (three females, five males) copied the conspecific demonstrator, which was significant (Binomial test: p  = 0.008 for each species). We additionally examined whether there was a difference in the latency to make the first choice between the birds that chose the demonstrated colour versus those that did not.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Two of seven jays (one male, one female) chose the same coloured cup (white) as the demonstrator (i.e., copied the demonstrator), while the other five jays (three females, two males) chose the non-demonstrated cup colour (black; Table 3). In comparison, Miller, Schwab & Bugnyar (in press) found that eight of eight crows (five females, three males) and eight of eight ravens (three females, five males) copied the conspecific demonstrator, which was significant (Binomial test: p  = 0.008 for each species). We additionally examined whether there was a difference in the latency to make the first choice between the birds that chose the demonstrated colour versus those that did not.…”
Section: Resultsmentioning
confidence: 92%
“…Homer touched both cups in session one and two, but passed criterion in session three. He was given four training sessions in total to ensure comparability with the number of demonstrator training sessions used for the carrion crows and ravens in Miller, Schwab & Bugnyar (in press). Homer chose the white cup 100% of the time during demonstrators for observers; therefore observers did not see any incorrect choices.…”
Section: Experiments 2: Two-choice Colour Discrimination Taskmentioning
confidence: 99%
See 3 more Smart Citations